2020
DOI: 10.1002/ejp.1522
|View full text |Cite|
|
Sign up to set email alerts
|

Opioids for chronic osteoarthritis pain: An updated systematic review and meta‐analysis of efficacy, tolerability and safety in randomized placebo‐controlled studies of at least 4 weeks double‐blind duration

Abstract: Background and Objective This updated systematic review evaluated the efficacy and safety of opioids compared with placebo for chronic osteoarthritis pain. Databases and Data Treatment Clinicaltrials.gov, CENTRAL, MEDLINE and PsycINFO were searched from October 2013 to July 2019. Randomized controlled trials comparing opioids with placebo and at least 4 weeks double‐blinded duration were analysed. Primary outcomes were pain relief of 50% or greater, disability, tolerability and safety. Effects were summarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 59 publications
1
33
1
1
Order By: Relevance
“…Treatment dissatisfaction with opioids may be related to the toxicity and low efficacy in OA that are well-recognized issues associated with this drug class. These results are consistent with those from RCTs showing that opioids provide limited benefit to patients with OA pain [11][12][13][14] and support the recently updated OARSI and ACR/AF guidelines, which strongly recommend against the use of opioids for managing OA pain [18,19].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Treatment dissatisfaction with opioids may be related to the toxicity and low efficacy in OA that are well-recognized issues associated with this drug class. These results are consistent with those from RCTs showing that opioids provide limited benefit to patients with OA pain [11][12][13][14] and support the recently updated OARSI and ACR/AF guidelines, which strongly recommend against the use of opioids for managing OA pain [18,19].…”
Section: Discussionsupporting
confidence: 86%
“…However, use of opioids to manage OA pain remains controversial. Results from randomized controlled trials (RCTs) demonstrated that opioids provide few benefits relative to other analgesics for relieving OA pain [11][12][13][14]. Furthermore, opioids are associated with a number of safety concerns, including toxicities and the risk of abuse and dependency [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…There is low to very low quality GRADE evidence from 22 RCTs of 4-26 weeks with 8,942 participants that opioids are superior in reducing pain and disability, inferior in tolerability and not different in safety compared to placebo for OA-pain (Welsch et al, 2020).…”
Section: (Supplementary Materials 1 and 2)mentioning
confidence: 99%
“…The results of the respective meta-analyses for CLBP, 33 osteoarthritis pain, 43 and neuropathic pain, 40 and open-label extension studies of these RCTs 3 were used for evidence-based recommendations for potential indications for opioids. The following primary outcomes were analysed: pain relief of 50% or greater, patient global impression to be much or very much improved, disability, dropout rates to adverse events (tolerability), frequency of serious adverse events, and death.…”
Section: Methodsmentioning
confidence: 99%